2006
DOI: 10.1111/j.1479-8425.2006.00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for traffic accidents in patients with obstructive sleep apnea syndrome

Abstract: A survey of traffic accidents incurred by 440 patients with obstructive sleep apnea syndrome determined the prevalence of traffic accidents in this group. The study also determined the independent risk factors for accidents in these patients with obstructive sleep apnea syndrome before and after the initiation of continuous positive airway pressure therapy. Before continuous positive airway pressure therapy, 43.4% of the patients had had traffic accidents. The independent risk factors for accidents were higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Such sleepiness may cause accidents and work‐related errors, as well as excessive sleepiness in untreated patients. We previously reported that patients with unimproved excessive daytime sleepiness even on CPAP treatment continued to have a high risk for traffic accidents 11 . In order to manage these symptoms and their related problems, the use of adjunctive central nervous system (CNS) stimulants, such as modafinil, has been proposed for patients with sleepiness on CPAP treatment based on the results of several clinical trials 20–24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such sleepiness may cause accidents and work‐related errors, as well as excessive sleepiness in untreated patients. We previously reported that patients with unimproved excessive daytime sleepiness even on CPAP treatment continued to have a high risk for traffic accidents 11 . In order to manage these symptoms and their related problems, the use of adjunctive central nervous system (CNS) stimulants, such as modafinil, has been proposed for patients with sleepiness on CPAP treatment based on the results of several clinical trials 20–24 .…”
Section: Discussionmentioning
confidence: 99%
“…The sleep study was done using previously described standard polysomnography technique and scoring 11–13 . After the diagnostic study was completed, the CPAP was titrated manually during an overnight polysomnography with the patient receiving CPAP.…”
Section: Methodsmentioning
confidence: 99%
“…Standard PSG techniques were used, as described previously 13 . The AHI was defined as the total number of apnea and hypopnea events divided by the total sleep time (TST) and was expressed as the number of events/h.…”
Section: Methodsmentioning
confidence: 99%
“…Standard PSG techniques were used, as described previously. 13 The AHI was defined as the total number of apnea and hypopnea events divided by the total sleep time (TST) and was expressed as the number of events/ h. Sleep staging and arousals were scored using 30 s epochs according to Rechtschaffen and Kales and American Sleep Association criteria. 14,15 The arousal index (ArI) was defined as the total number of arousals divided by the TST, and was expressed as the number of events/h.…”
Section: Study Protocolmentioning
confidence: 99%
“…In Canada, there is no direct cost to the patient, though there is a cost to society of an acute care hospital bed of 600$ plus a consultation with a respirologist of 200$. There are health and social consequences in foregoing diagnosis and treatment: studies conducted by George et al [33] and Yoshino et al [34] show a relationship between moderate to severe sleep apnea and motor vehicle accidents. The Canadian Medical Association's guidelines to physicians titled "Determining Medical Fitness to Operate Motor Vehicles", identifies sleep disorders as a reason for the suspension of a drivers license [35], To this end the Ontario Health Insurance Program now subsidizes 75% of the cost of a continuous positive airway pressure (CPAP) device which is the standard accepted treatment for OSA [36].…”
Section: Challenges With Psgmentioning
confidence: 99%